2012
DOI: 10.22495/cocv10i1c7art3
|View full text |Cite
|
Sign up to set email alerts
|

Accrual quality: The presence of women directors on audit committee boards

Abstract: This article examines whether the participation of women on audit committee boards enhances audit committee effectiveness to control earnings management practices. While numerous studies have investigated the effects of women audit committee on earnings management, empirical evidence is rather inconsistent. Therefore, it is imperative to investigate the impact of female representation on audit committee effectiveness. In order to address the objective of the study, we use cross-sectional version of the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
11
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 18 publications
12
11
4
Order By: Relevance
“…It is also found that LEV is positively and significantly related to ABSDA1 and ABSDA2. This positively significant result is consistent with previous studies (Al-Rassas & Kamardin, 2016;Saleh et al, 2005Saleh et al, , 2007Salleh & Haat, 2013;Salleh et al, 2012). This is because companies that face financial difficulties attempt to report higher returns in order to hide their financial constraints (Campa, 2015;Park & Shin, 2004).…”
Section: Regression Modelssupporting
confidence: 90%
See 3 more Smart Citations
“…It is also found that LEV is positively and significantly related to ABSDA1 and ABSDA2. This positively significant result is consistent with previous studies (Al-Rassas & Kamardin, 2016;Saleh et al, 2005Saleh et al, , 2007Salleh & Haat, 2013;Salleh et al, 2012). This is because companies that face financial difficulties attempt to report higher returns in order to hide their financial constraints (Campa, 2015;Park & Shin, 2004).…”
Section: Regression Modelssupporting
confidence: 90%
“…This result is in line with Abdul-Rahman & Ali (2006), Mansor et al (2013), Saleh et al (2005), Saleh et al (2007) and Salleh et al (2012). It may be because large firms are seriously reviewed by the external capital markets and analysts compared to small firms (Park & Shin, 2004).…”
Section: Regression Modelssupporting
confidence: 83%
See 2 more Smart Citations
“…The characteristics of women on the audit committee can reduce earnings management. This is supported by research conducted by Thiruvadi & Huang (2011), Qi & Tian (2012), Salleh et al (2012), Susanto (2016), and Florencea & Susanto (2019). The opposite was obtained from research conducted by Loualalen et al (2015), and Abdullah & Ismail (2016) found that gender on the audit committee had no effect on earnings management.…”
Section: Introductionmentioning
confidence: 83%